(untitled) (Revista Contexto & Educação, 2022)
By thinking about Why do I teach in the way I do? It has provided reflection about the choices as a Chemistry teacher (first author). On this autobiographical narrative research, the aim is to understand if the reflexive movement through the lived experience may take root in a self-education process as well as contribute to think about teachers education and Chemistry teaching. The analysis are guided, from the categories (i) school experiences – student and teacher; (ii) teaching loneliness – closed door; (iii) continuing training – opened door; (iv) the collective – other subjects. Such categories provided the following discussion: a) first teachers education stories and teaching: from the school desk to the closed door; b) opened door: the continuing teachers education; c) education and teaching professionalization: contributions to the collective subject. The analysis enabled to understand that the lived, when is guided by reflection, it may contribute to teachers education, since it is considered as an important tool of awareness. The results has shown: (1) the school is a place where it is possible to learn about teaching; (2) research and reflection are inseparable from the teachers education and teaching practices; (3) partnerships empower the collective building of new practices.